Application of calcium lignosulphonate as an environmentally friendly depressant in the Cu–As separation by froth flotation at low alkalinity. (20th June 2023) - Luo, Yuanjia; Xia, Yuqin; Wang, Changtao; Chen, Jianhua; Ou, Leming
Abstract: The removal of arsenic has been an important issue due to the considerable harm that arsenic contamination does to the ecosystem, in this paper, calcium lignosulphonate (CLS) was the first time introduced as an environmentally friendly inhibitor for the selective Cu–As separation by froth flotation at low alkalinity, and its separation effect and mechanism was researched by flotation experiments, XPS measurements, and first-principles calculations. The single mineral and mixture mineral flotation experiment results consistently indicated that CLS can effectively realize the selective separation of arsenopyrite and chalcopyrite. The results of XPS experiment and first-principles calculation consistently indicated that CLS was selectively chemisorbed on the Fe site on the surface of arsenopyrite by forming the Fe–O bond through the interaction between sulfonate group (-SO3 ) in its structure and surface Fe atom. However, the chemisorption of CLS on the Fe site on chalcopyrite surface was not found. Moreover, the CL 2− adsorption on arsenopyrite surface also can be promoted due to more attached Ca ion site while that on chalcopyrite surface remained weak due to the less attached Ca ion site. Overall, more LS 2− adsorption on the Fe site and attached Ca ion site on arsenopyrite surface caused the selective depression of arsenopyrite.